2014
DOI: 10.1097/mcg.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethnicity in Upper Gastrointestinal Hemorrhage

Abstract: Goals To examine ethnicity's role in the etiology and outcome of upper gastrointestinal hemorrhage (UGIH). Background UGIH is a serious condition with considerable associated morbidity and mortality. Study We analyzed 2196 patients admitted with acute UGIH between January 2006 and February 2012. Complete clinical data was gathered prospectively and entered into our GI Bleed Registry, which captures demographic and clinical variables. Results were analyzed using the Chi-square analyses and the analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
4
23
0
1
Order By: Relevance
“…It is a frequent cause of hospitalization, although a number of advances have been made in diagnosis and treatments. Studies from the United States indicated that hospitalizations for upper GI (UGI) hemorrhage in the early 1990s occurred at an annual incidence of ~100/100,000 population and were ~5 times more common than hospitalizations for lower GI hemorrhage (5)(6)(7)(8)(9). UGI hemorrhage usually causes fatalities in 6-14% of those it affects (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It is a frequent cause of hospitalization, although a number of advances have been made in diagnosis and treatments. Studies from the United States indicated that hospitalizations for upper GI (UGI) hemorrhage in the early 1990s occurred at an annual incidence of ~100/100,000 population and were ~5 times more common than hospitalizations for lower GI hemorrhage (5)(6)(7)(8)(9). UGI hemorrhage usually causes fatalities in 6-14% of those it affects (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…1 In studies done in Western population, as well as Southern and coastal India, peptic ulcer disease still constitutes the most common cause of upper gastrointestinal bleed. [2][3][4][5] Upper gastrointestinal endoscopy plays an important role in the diagnosis of etiology of bleed, stratification of patients according to the risk of rebleed based on the endoscopic stigmata and in treatment of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 Our observation on racial differences may, but only in part, be explicable given that Hispanic patients are reported at higher risk of variceal re-bleeding, and in our population, there was a significant association between liver diseases with readmission. 10 In our cohort of patients, the presence of chronic comorbidity correlated with the likelihood of ED readmission with complications; specifically, the presence of chronic liver disease and chronic gastrointestinal disease were significantly associated with ED readmission. These observations are not surprising as comorbidities define medical frailty that in turn strongly influences anesthesia outcome.…”
Section: Discussionmentioning
confidence: 69%
“…We can only speculate that our observations may reflect true pathophysiological differences, socioeconomic stressors or cultural norms that impact communication, availability of alternative primary care support, and proximity to the institution where the procedure took place . Our observation on racial differences may, but only in part, be explicable given that Hispanic patients are reported at higher risk of variceal re‐bleeding, and in our population, there was a significant association between liver diseases with readmission …”
Section: Discussionmentioning
confidence: 75%